Structural and optical properties of (Y3+, Tb3+)-codoped sodium bismuth titanate nanoparticles. (June 2021) - Jeshurun, Ashok; Irfan Mohammad; Behara, Santosh; Bogala, Mallikharjuna Reddy
Abstract: The present study investigates the effect of (yttrium, terbium) ions codoping on structural and optical properties of sodium bismuth titanate (Na0.5 Bi0.5 TiO3 or NBT) with the possible practical application as a multi-luminescence material in optoelectronic devices such as light-emitting diodes. The polycrystalline samples of Na0.5 (Y/Tbx Bi1-x )0.5 TiO3 (x = 0.00, 0.04, 0.06, and 0.08) were synthesized using solid-state reaction (mixed oxide) technique. Stoichiometric amounts of metal compounds (Na2 CO3, Y2 O3, Tb4 O7, Bi2 O3, and TiO2 ) were mixed via ball milling at 250 rpm for 2 h, and the ground powders were calcined at 700 °C for 2 h. The powders were pressed under uniaxial pressure of 6.87 MPa to obtain green pellets, which were later sintered at 1, 000 °C for 2 h to obtain the Na0.5 (Y/Tbx Bi1-x )0.5 TiO3 samples. X-ray diffraction analysis suggests that the perovskite phase is established for all (Y 3+, Tb 3+ )-codoped NBT compositions (x = 0.00–0.08). The presence of NBT functional groups was confirmed by Fourier transform infrared spectroscopy. Raman spectra indicate that (Y 3+, Tb 3+ ) ions induce minor changes to the crystal lattice structure, with no disturbance to the long-range order. X-ray photoelectron spectroscopy results reveal the presence of all the constituent elements in the NBT samples. Scanning electron microscopy confirms the polycrystalline nature of the samples with uniform distribution of multifacetted or nearly spherical grain structures. Transmission electron microscopy and selected area electron diffraction (SAED) images show the presence of nanocrystals in the samples. Ultraviolet diffuse reflectance spectroscopy (UV-DRS) and photoluminescence results illustrate that Na0.5 (Y/Tbx Bi1-x )0.5 TiO3 possess wider optical energy band gap (Eg  = 3.23–3.27 eV) with promising luminescence applications in the optoelectronic industry. Highlights: (Y 3+, Tb 3+ )-codoped sodium bismuth titanate nanoparticles were prepared for the first time by the metal oxide mixing method. X-ray diffraction study reveals the formation of good quality and stable (Y 3+, Tb 3+ )-codoped Na0.5 Bi0.5 TiO3 (NBT) crystals. Spectroscopy and microscopy results confirm the effective doping of (Y, Tb) metals in NBT crystal lattice. (Y 3+, Tb 3+ )-codoped NBT emits green photoluminescence light with potential use in optoelectronics (light-emitting diodes).